Pengaruh Konsumsi, Produksi, Kurs Dollar AS dan PDB Pertanian Terhadap Impor Bawang Putih Indonesia - Indrayani, Ni Kadek Ayu; Swara, I Wayan Yogi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 5, Mei 2014 (pp.173- 226), 2014)
As an agricultural country, Indonesia has great potentials in the agricultural sector. But nowadays,the problem occurred in the agricultural sector is quite disturbing indonesian's economic. The increasing of horticultural products import, showed as if horticultural products could not compete. Based on data from BPS, horticultural commoditiy imported highest is garlic. This research intended to determine the influence of consumption, production, U.S. dollar exchange rate and the GDP of agriculture to the import of garlic in  Indonesia. Besides that, this research also aimed to determine the variables that most affected the import of garlic, which used linear regression analysis. The results showed that consumption, production, U.S. dollar exchange rate and the GDP of agricilture effected simutaniosly and significant to the import of garlic. Then partially, consumption and the GDP of agriculture has significant and positive effect to the import of garlic. Production and the U.S. dollar exchange rate had no significant effect and the variables that most affected to the import of garlic in indonesia is GPD of agriculture.
Keywords: The import of garlic; consumption; production; U.S. dollar exchange rate; the GDP of Agriculture